Monetary Policy Rules in Central and Eastern Europe - Michael Frömmel; Franziska Schobert (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2006)
We estimate monetary policy rules for six central and eastern European countries (CEEC) by taking changes in the policy settings explicitly into account. Distinguishing rather fixed and more flexible exchange rate arrangements we find that for most countries exchange rates played an important role in monetary policy during the fixed exchange rate regime, whereas their influence disappears after the introduction of floating exchange rate regimes. This indicates that most countries followed their officially announced policy settings. For Slovenia and to some extent for Romania, however, we find evidence for exchange rate targeting, although they officially announced a managed float.
Keywords: P20; E58; E52; 330; monetary policy; Taylor rules; transition economies; CEEC; inflation targeting; interest rate policy